California dreaming : ideology, society, and technology in the citrus industry of Palestine, 1890-1939 - Karlinsky, Nahum (Albany : State University of New York Press, 2005)
Multidisciplinary study of the citrus industry in Palestine before World War II.
CHAPTER THREE. SPATIAL DISTRIBUTION AND SOCIAL AND ENTREPRENEURIAL PROFILE -- CHAPTER FOUR. FROM JAFFA TO PETAH TIKVA -- CHAPTER FIVE. TECHNOLOGICAL INNOVATION DURING THE MANDATE ERA -- CHAPTER SIX. TECHNICAL INNOVATIONS IN ARAB CITRICULTURE -- CHAPTER SEVEN. PURSUIT OF PROFIT -- CHAPTER EIGHT. THE BRITISH MANDATE GOVERNMENT'S POLICY TOWARD THE CITRUS INDUSTRY -- CHAPTER NINE. ATTEMPTS TO ESTABLISH A CARTEL -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z.
Based on author's doctoral thesis, Hebrew University, 1995.
Includes bibliographical references (pages 247-265) and index.
Print version record.
English.
JSTOR
Keywords: Citrus fruit industry -- Palestine -- History; Fruit trade -- Palestine -- History; Entrepreneurship -- Palestine -- History; Agrumes -- Industrie -- Palestine -- Histoire; Entrepreneuriat -- Palestine -- Histoire; BUSINESS & ECONOMICS -- Industries -- Agribusiness; TECHNOLOGY & ENGINEERING -- Agriculture -- Sustainable Agriculture; Citrus fruit industry; Entrepreneurship; Fruit trade; Middle East -- Palestine; History